2017
DOI: 10.1149/2.1491706jes
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Study of the Electrochemical Migration of Tin under Bipolar Square Wave Voltage

Abstract: The electrochemical migration (ECM) of tin under bipolar square wave voltage with various time periods was in situ studied using optical and electrochemical techniques. The results show that there is no dendrite growth but only precipitate formation for the time periods from 1 to 100 s during the same test time interval. The amount of precipitates increases with the increasing time period from 1 to 100 s. Moreover, the locations where the precipitates appear are time period dependent. As the time period increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Therefore, the AC could also be expected to inhibit the ECM of Sn and Sn solder alloys. Zhong et al 154 also found that the dendrite growth of Sn under bipolar square wave voltage (like AC voltage) was strongly dependent upon the semi-cycle of bipolar square wave voltage. The dendrite growth will not appear if the semicycle is shorter than a critical value.…”
Section: 158mentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, the AC could also be expected to inhibit the ECM of Sn and Sn solder alloys. Zhong et al 154 also found that the dendrite growth of Sn under bipolar square wave voltage (like AC voltage) was strongly dependent upon the semi-cycle of bipolar square wave voltage. The dendrite growth will not appear if the semicycle is shorter than a critical value.…”
Section: 158mentioning
confidence: 97%
“…49,155,156 According to the ECM mechanisms of Sn and Sn solder alloys and the previous studies regarding the ECM and its inhibition of other materials, 15,[152][153][154][155][156][157][158][159][160][161] the possible strategies to inhibit the ECM of Sn and Sn solder alloys are summarized, including adding alloy elements, inhibitor, and pulsed or AC voltage.…”
Section: Inhibition Of Ecm Of Sn and Sn Solder Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…The same electrolyte was also added into the plexiglass chamber to minimize the evaporation. This setup which is similar to those reported in previous work about atmospheric corrosion or ECM makes it possible to perform in situ electrochemical migration measurements under thin electrolyte layer [13][14][15].…”
Section: Materials and Setup For Electrochemical Migration Testmentioning
confidence: 70%